The Return to In-person Education Post-pandemic: Perceptions and Expectations of University Students - Peinado, Jurandir (2024)
The Covid-19 pandemic has forced organizations and governments to adopt social distancing measures, such as transferring their face-to-face activities to the remote model, mediated by Information and Communication Technologies (ICT). However, the advent of vaccines and other protocols allowed the possibility of several activities, including education, to return to the face-to-face model. This context demands for research to investigate this post-pandemic scenario. The objective of this article was to survey and analyze the perceptions and expectations of students at a Brazilian public university, facing the possibility of returning to classes in the face-to-face model. Through a questionnaire sent to university students, the group of researchers used the content analysis technique to code and categorize 987 responses received through a Survey. It was observed that the students' responses involved aspects directly linked to the teaching and learning process (endogenous), as well as aspects that touch this process (exogenous).      Keywords: Post-pandemic; Students; Public university; Return to in-person teaching.